Paradygmat Weberowski w myśli religioznawczej Petera Bergera - Iwanicki, Juliusz (Polskie Towarzystwo Religioznawcze, 2011)
Juliusz Iwanicki – WEBER’S PARADIGM IN PETER BERGER’S STUDY OF RELIGION In the article I analyze the paradigm of Max Weber in study of religions. This paradigm consists of such ideas as: historicism, comparative study, relation of religion and society, or anal-ysis of rationalization processes in Western culture. One of the main followers of Max Weber’s thought was Peter Berger. This American scholar initially was a supporter of the classical theory of secularization. He understood the theory of secularization as a continuation of rationalization processes. In his later works, however, he modified his theory. He concluded that the seculariza-tion theory is correct only for selected areas. The effect of Max Weber’s thought is also visible in this phase of Berger’s work.